Análise do custo do ciclo de vida para comparar estratégias de manutenção de cardans de laminador de tiras à frio - Cristofari Junior, Carlos Alberto (2017)
The Brazilian steel industry is facing an adverse scenario with direct competition from global emerging markets. This scenario forces companies to turn their attention on their internal processes to obtain and sustain competitive advantage over their competitors. The Asset Management approach brings an alignment across all business processes to what adds value to the business and optimizes the asset economic life. Therefore, reliability engineer offer a set of tools as a means to manipulate asset usage information, bringing to understandment the assets behavior and their interactions throughout their life cycle. In such way this particular work has proposed to study the life cycle cost of a specific asset (cold strip mills cardam shafts) in order to modeling reliability, maintainability and costs data to simulate alternative asset management strategy. The major results of this study are the reliability, mantenability and cost analysis of cardans shafts, the compering of run to failure strategy with three scenarios of schedule restoration task and all information generated to contribute with asset management.